Quadrivalent versus trivalent influenza vaccine: clinical outcomes in two influenza seasons, historical cohort study. (January 2020) - Shasha, D.; Valinsky, L.; Hershkowitz Sikron, F.; Glatman-Freedman, A.; Mandelboim, M.; Toledano, A.; Paran, Y.; Ben-Ami, R.; Goldman, D.
Abstract: Objectives: The quadrivalent influenza vaccine (QIV) contains two influenza B antigens (one of each B lineage), while the trivalent vaccine (TIV) contains solely one. As a result, a mismatch between the circulating B lineage and the lineage in the TIV occurs frequently. We aimed to compare the frequency of clinically significant outcomes in a large cohort of vaccinees receiving either TIV or QIV. Methods: Historical cohort study of all inactivated influenza vaccinees (aged 3 years and older) in a Health Maintenance Organization insuring 1.2 million individuals, over two influenza seasons in which both vaccines were provided non-selectively. Primary outcome was hospital admissions during the influenza season. Multivariate analysis was performed using logistic regression to adjust for relevant covariates. Results: Our cohort included 150 518 and 168 296 vaccinees in the first (S1) and second season (S2), respectively. The two influenza seasons were characterized by high Influenza B activity. Of those vaccinated with QIV, 2074 of 49 726 (4.2%) and 6563 of 121 741 (5.4%) were hospitalized compared with 7378 of 100 792 (7.3%) and 3372 of 46 555 (7.2%) of those vaccinated with TIV (S1 and S2, respectively). After multivariate analysis adjusting for several covariates (gender, age, socioeconomic status, chronic morbidity, timing of vaccination), compared with TIV recipients, QIV vaccinees had lower odds for hospitalization (OR = 0.92, 95% CI 0.87–0.98 and OR = 0.89, 95% CI 0.85–0.93) or emergency department visit (OR = 0.91, 95% CI 0.87–0.95 and OR = 0.84, 95% CI 0.81–0.87) in S1 and S2, respectively (p < 0.001). Lower odds of mortality and influenza-like illness were also observed in S2 (OR = 0.61, 95% CI 0.50–0.75 and OR = 0.92, 95% CI 0.90–0.95, respectively). Conclusions: In seasons with relatively high influenza B activity, QIV appeared more protective than TIV in Israel.